Pelaksanaan Kegiatan P2K2 Untuk Pengelolaan Keuangan dan Rencana Usaha Keluarga di Masa Pandemi - Niko Akbar; Mochammad Arief Hermawan Sutoyo (AJAD : Jurnal Pengabdian kepada Masyarakat, 2022)
During this pandemic, of course, many people and especially poor families will feel economic difficulties due to being affected by the pandemic. This is driven by a decline in financial literacy and not knowing how to properly manage finances and problems that will arise in the future. The author raises the idea of forming a solution, namely the Implementation of P2K2 Activities. This activity was held in collaboration with the Batanghari District Social Service. This activity can provide basic knowledge and hone skills in managing income and expenses, as well as business planning. The method used is the socialization and training of PKH participants. The expected result of this service is that holding this activity it can provide benefits for families affected by the pandemic to have better financial management abilities during this pandemic.